Agreement test between Ziehl Neelsen staining and GenXpert in adult pulmonary tuberculosis diagnosis - Kemas Ya'kub Rahadiyanto; Muhammad Syahrul Ramadhan; Ella Amalia (Faculty of Medicine, Universitas Islam Indonesia, 2021)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (MTB). Most of healthcare facilities in Indonesia still use Ziehl Neelsen (ZN) staining to diagnose pulmonary tuberculosis (TB) rather than GeneXpert MTB/RIF. However, the agreement between both methods is not well established.Objective: This study aims to observe levels of agreement between ZN staining and GeneXpert MTB/RIF in diagnosing adult pulmonary TB at Dr. Mohammad Hoesin General Hospital (RSMH) Palembang.Methods: This study was a retrospective comparative analytical study using an agreement test. Its samples were patient specimens for a period of January 2016 - March 2017 which were examined by ZN staining and GeneXpert MTB/RIF to diagnose pulmonary TB at the Clinical Pathology and Microbiology Installation of RSMH Palembang. Its data were obtained from laboratory results of ZN staining and GeneXpert MTB/RIF. Then, Cohen’s Kappa was used to measure the levels of agreement between both the assays.Results: Of 150 specimens, 69.3% were from male patients and 30.7% were from female patients with mean age of 46.71±14.57. Both ZN staining and GeneXpert positivity were 57.3%. 0.05% of positive GeneXpert MTB/RIF were negative ZN smear, while 0.06% of negative GeneXpert were positive ZN smear. The Cohen’s Kappa coefficient was 0.893 indicating a very good agreement.Conclusion: This study found that there was a very good agreement between ZN staining and GeneXpert MTB/RIF in diagnosing adult pulmonary TB at the RSMH Palembang.